4-3t=2t-20

Simple and best practice solution for 4-3t=2t-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-3t=2t-20 equation:


Simplifying
4 + -3t = 2t + -20

Reorder the terms:
4 + -3t = -20 + 2t

Solving
4 + -3t = -20 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
4 + -3t + -2t = -20 + 2t + -2t

Combine like terms: -3t + -2t = -5t
4 + -5t = -20 + 2t + -2t

Combine like terms: 2t + -2t = 0
4 + -5t = -20 + 0
4 + -5t = -20

Add '-4' to each side of the equation.
4 + -4 + -5t = -20 + -4

Combine like terms: 4 + -4 = 0
0 + -5t = -20 + -4
-5t = -20 + -4

Combine like terms: -20 + -4 = -24
-5t = -24

Divide each side by '-5'.
t = 4.8

Simplifying
t = 4.8

See similar equations:

| 45x+9x=0 | | 43=7+y | | -4(4y-4)-y=-4(y-3) | | 7x^4-33x+26=0 | | 18(2-3)-2x=2x | | 6x+6=3(x+9) | | 2n+9=15 | | 4n+1=-23-2n | | g(x)=-f(-4) | | 3x-2y=-7 | | 6-7j=2j+3 | | 25W^2+10W+1=0 | | 5x+9=2(2x+3) | | -5x(4x-8y+4)= | | 3u+45=9(u+9) | | 2x^2+14x-144=0 | | -3x+5+6(x+1)=-2+3 | | 2(x+2)+4x=x+6 | | 9+c=-13 | | 4(s+2)-s=3(s+1) | | t=4n+4v | | 0.3(y+1)-0.4(3-2y)=0.2 | | 7x+5-4x-4=x | | (5cd^2)(-c^4d)= | | n^2+n+132=0 | | 2.5x+2.1=5.3 | | 5z^2-35=0 | | -4x^2+3x+10=0 | | 3u+45=9u+81 | | 3x-5=3(x+9) | | -3(x+1)+4x=13 | | 6y-6=48 |

Equations solver categories